Vector orthogonal frequency division multiplexing system over fast fading channels. Issue 13 (1st September 2014) - Zhou, Wen; Fan, Lisheng; Chen, Hongbin
Abstract : The performance of the vector orthogonal frequency division multiplexing (V‐OFDM) system over fast fading channels is investigated. The channel is time varying within one V‐OFDM data‐block period, which causes the inter‐carrier interference (ICI). With the help of an equivalent V‐OFDM system model and an auxiliary transform matrix, a novel mathematical expression for the received signal with the ICI signal is derived, which clearly expresses how the signal of a target vector block (VB) is interfered by other VBs. The ICI signal is analysed and two theorems about its property are proposed. The first theorem presents the expression of the power of the ICI signal, showing that the ICI signal power increases with the VB number. The other one indicates that ICI signals at different subcarriers are not correlated. With the two theorems, a novel detection method utilising the correlation of the ICI signal is therefore proposed. Numerical results verify the validity of the derived theorems and simulation results demonstrate that the proposed minimum mean square error (MMSE) detection can suppress the ICI effect and it is superior to the conventional MMSE detection in terms of both detection mean square error and bit error rate performance.